Between Justice and Regularity Between Justice and Regularity in Distance Education Homeschooling and Community Partnerships Solutions in the Light of the COVID-19 Pandemic - Alarifi, Hessah Saad; ALjuwayid, Mashael Saleh; Quraishi, Wafa Abdulrahman (Technium Social Sciences Journal, 2021)
In Saudi Arabia, education has been transformed in light of the Corona pandemic into distance education through digital platforms, and the state has secured a good technical infrastructure for this. And it became the compulsory educational style for all groups of students with a large number of different requirements and mandatory daily attendance. The research team noticed the inability of some groups of students to keep pace with the requirements of distance education, which reduces the opportunities for justice in education for students, especially at the primary level. Accordingly, the research team used the qualitative method between analyzing UNESCO documents on education fairness and applying the interview tool to seventeen interviews of primary school leaders who were randomly selected (one school from each school district). A full year of learning about each other under the pandemic. The study found that not all students were able to obtain the same educational opportunities, and they were classified according to two categories: The first category is students who suffer from difficulty accessing the Internet, or their parents’ ignorance of technology, or their poor social level, which hinders them from securing educational supplies. distance. As for the second category, they are outstanding students with special social conditions between the separation of parents or orphans and others, so that the student can master learning at home, but he cannot attend daily on the platform or follow up on the submission of mandatory distance education requirements. The research team suggested adopting home education at the primary level for those who wish to it, and providing community partnership as solutions to achieve justice in education for all groups of students at the primary level.